The Effects of Captioning Videos Used for Foreign Language Listening Activities - Paula Winke; Susan Gass; Tetyana Sydorenko (Language Learning and Technology, 2010)
This study investigated the effects of captioning during video-based listening activities. Second- and fourth-year learners of Arabic, Chinese, Spanish, and Russian watched three short videos with and without captioning in randomized order. Spanish learners had two additional groups: one watched the videos twice with no captioning, and another watched them twice with captioning. After the second showing of the video, learners took comprehension and vocabulary tests based on the video. Twenty-six learners participated in interviews following the actual experiment. They were asked about their general reactions to the videos (captioned and noncaptioned). Results from t-tests and two-way ANOVAs indicated that captioning was more effective than no captioning. Captioning during the first showing of the videos was more effective for performance on aural vocabulary tests. For Spanish and Russian, captioning first was generally more effective than captioning second; while for Arabic and Chinese, there was a trend toward captioning second being more effective. The interview data revealed that learners used captions to increase their attention, improve processing, reinforce previous knowledge, and analyze language. Learners also reported using captions as a crutch.